(untitled) (West African Journal on Sustainable Development, 2024)
The study examined the level of awareness and perception of Nigerian undergraduate students on the United Nations sustainable development goals using gender, level of education and university type as variables. The study adopted descriptive method to evaluate awareness of undergraduates and their perception regarding sustainable development goals. It was conducted in the two public universities in Anambra state with a population of 20,626 undergraduate students. The sample of 392 students was composed using simple Yamane formula and simple random sampling technique. Two research questions guided the study. The reliability of 0.82 was ascertained through test retest. Data were collected using two instruments; Sustainable Development Awareness scale and Sustainable Development Knowledge Scale. Data collected were analyzed using percentages and represented graphically. It was revealed that the level of awareness and perception of female undergraduate students with 47.5% was greater than the level of awareness and perception of their male counterparts with 48.8%. Also, it indicated that 300L undergraduate students were more aware than 200L undergraduate students with 55.7% and 37.5% respectively among others. It recommended the institutionalization of sustainable development studies in the universities, adoption of innovative strategies to increase awareness of male students, organization of action-based programmes to enhance awareness and perception towards sustainable development goals among undergraduate students in Nigerian university among others.